Studi literatur: Efektivitas model problem-based learning terhadap keterampilan argumentasi ilmiah peserta didik pada pembelajaran sains - Putri Nirmala; Siti Shofa Assyifa’ul Qulbi Barid; Sri Rejeki Dwi Astuti; Sri Wahyuni (Papanda Publisher, 2026)
Students’ scientific argumentation skills are not yet optimally developed because classroom learning is still dominated by teacher-centered activities. Students tend to memorize material rather than practice constructing evidence-based arguments. Problem Based Learning (PBL) is considered an effective innovative learning approach as it emphasizes active student involvement in solving real-world problems through group discussions, with the teacher acting as a facilitator. This study aims to analyze the effectiveness of PBL in enhancing students’ scientific argumentation skills. A Systematic Literature Review (SLR) using the PRISMA method was conducted. Articles were searched through Google Scholar using the keywords “Problem Based Learning,” “Scientific Argumentation,” and “Science.” The search yielded 354 articles, which were screened based on publication year (2019–2025), full-text availability, language, and topic relevance. Fifteen articles met the inclusion criteria and were analyzed descriptively. The results indicate that PBL effectively improves students’ scientific argumentation skills at the elementary, junior, and senior high school levels. The quality of argumentation can be further enhanced by using interactive media, such as PowerPoint, virtual simulations, and student worksheets (LKPD), as well as learning approaches like Socio-Scientific Issues and Flipped Classroom.